A CASE OF PRIMARY HYPERPARATHYROIDISM COEXISTING WITH MONOCLONAL GAMMOPATHY OF UNDETERMINED SIGNIFICANCE (MGUS) - Chan, Lim Fang; Miao, Tan Jia; Ching, Tee Hwee; Hatta, Siti Nabihah Mohamed (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypercalcemia is a relatively common clinical problem in hospitalized patients. Primary hyperparathyroidism and plasma cell dyscrasias such as multiple myeloma and monoclonal gammopathy of undetermined significance (MGUS) are known to be the most common causes of hypercalcemia. Although the occurrence of these disorders in one patient has been reported previously, it is still believed to be a rare phenomenon. We report a case of hypercalcemia, resulting from coexistent primary hyperparathyroidism and MGUS. CASE A 45-year-old female with no previous medical illness was admitted for symptomatic hypercalcemia. A review of symptoms during admission was significant for constipation, nausea, anorexia, polyuria and thirst. Initial blood investigations showed hypercalcemia (corrected calcium 4.43 mmol/L), renal impairment (creatinine 154 mmol/L) and anaemia (haemoglobin 9 g/dL). Hypercalcemia was managed with intravenous hydration, bisphosphonates and furosemide. Subsequent tests include elevated intact parathyroid hormone (820.4 pg/ml) and an elevated 24-hour urinary calcium/creatinine clearance ratio of 0.07, suggestive of primary hyperparathyroidism. This was further supported by the finding of a right parathyroid adenoma on neck ultrasound. Due to an abnormal albumin/globulin ratio of 0.89, serum protein electrophoresis was also done which revealed IgG lambda paraproteinemia. The skeletal survey and bone scan were normal. Bone marrow and trephine biopsy showed the presence of clonal plasma cells at less than 10 percent, which confirmed the diagnosis of MGUS. The patient is currently under multidisciplinary care in endocrinology and haematology subspecialties. Sestamibi parathyroid scan has been arranged for preoperative localization. She is also being monitored closely for progression to multiple myeloma. CONCLUSION This case gives significant insights into potential concomitant causes of hypercalcemia. A high index of suspicion and a systematic approach to performing relevant screening tests are essential, as earlier diagnosis leads to improved clinical outcomes.